CORRELATION BETWEEN FAST FOOD CONSUMPTION AND OBESITY IN WOMEN OF FERTILIZING AGE IN TUBAN, EAST JAVA - Prasiwi, Nikita; Tysa Runingsari (International Nutrition and Health Administrations Journal, 2025)
Obesity is a condition with excessive fat accumulation due to an imbalance between energy intake and energy used over a long period. This study aimed to determine the relationship between fast food consumption and obesity in women of childbearing age. This study uses an analytical research method with a cross-sectional approach. The population of this study was the population of this study was 234, with a sample of 148 respondents, determined using a simple random sampling technique. The Independent variable is fast food consumption, dependent variable is obesity. The research analysis uses Spearman's correlation statistical test. The research showed that some respondents had a frequency of fast-food consumption in the bad category. The results of statistical tests show that there is no significant relationship between fast food consumption and obesity with p-value = 0.341 > 0.05. Although fast food consumption in the bad category did not show a significant relationship with obesity, other factors such as genetic factors, socioeconomic status, and environmental influences still play a role in obesity risk. Other factors can influence obesity such as genetic factors, socioeconomic status, environmental factors, and also the use of contraception.